Daya Gabung dan Heterosis Ketahanan Pepaya (Carica papaya L) terhadap Penyakit Antraknosa*) - Hafsah, Siti; astrosumarjo, Sarsidi S; Sujiprihati, Sriani; Sobir, ,; Hidayat, Sri Hendrastuti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2007)
This study was conducted to determine the relative importance of general (GCA) and specific (SCA) combining ability and heterosis effects on resistance to C. gloeosporioides in selected papaya genotypes. A half diallel mating scheme of five genotypes of papaya were evaluated in the field. The combining ability analysis revealed that both the additive and nonadditive gene effects were present. Crosses between the resistance and susceptible genotypes showed intermediate disease reaction to papaya anthracnose disease (PAD) suggesting a polygenic system of resistance to the disease. Highly resistance heterosis of 51.51% at Tajur and 48.71% at Gunung Geulis were expressed in crosses between IPB5 x PB000174. Key words: Papaya, anthracnose, GCA, SCA, heterosis